1990
DOI: 10.1111/j.1365-2826.1990.tb00396.x
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical and Immunocytochemical Assessment of Neural Progestin Receptors Following Estradiol Treatments that Eliminate the Sex Difference in Progesterone‐Facilitated Lordosis in Guinea‐Pigs

Abstract: A single injection of estradiol benzoate (10 pg), while highly effective in ovariectomized female guinea-pigs, does not prime castrated males to display progesterone-facilitated lordosis. In contrast, adult males and females exhibit the same, high degree of progesterone-facilitated lordosis when primed with two, 2.0 pg injections of free estradiol-17B (pulse regimen). We compared neural progestin receptor induction after these different estradiol treatments by in vitro radioligand binding assays and imrnunocyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
1

Year Published

1990
1990
2013
2013

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 42 publications
(37 reference statements)
2
16
1
Order By: Relevance
“…This idea is also supported by the strong correlation of VLH PR-IR and behavioral sensitivity to progesterone following estradiol pulses (Olster and Blaustein, 1990a) and during progesterone-induced desensitization (Blaustein and Turcotte, 1990). This region may be analogous to the rat ventrolateral subdivision of the ventromedial nucleus of the hypothalamus (VL-VMN) , which is also behaviorally responsive to estradiol and progesterone (Rubin and Barfield, 1983a,b), and which contains a dense population of estrogen- (Stumpf, 1968;Pfaff and Keiner, 1973) and progestin-concentrating cells ( Warembourg, 1978;Sar, 1988;Fox, Harlan, Shivers, and Pfaff, 1990).…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…This idea is also supported by the strong correlation of VLH PR-IR and behavioral sensitivity to progesterone following estradiol pulses (Olster and Blaustein, 1990a) and during progesterone-induced desensitization (Blaustein and Turcotte, 1990). This region may be analogous to the rat ventrolateral subdivision of the ventromedial nucleus of the hypothalamus (VL-VMN) , which is also behaviorally responsive to estradiol and progesterone (Rubin and Barfield, 1983a,b), and which contains a dense population of estrogen- (Stumpf, 1968;Pfaff and Keiner, 1973) and progestin-concentrating cells ( Warembourg, 1978;Sar, 1988;Fox, Harlan, Shivers, and Pfaff, 1990).…”
Section: Discussionmentioning
confidence: 88%
“…We and others have found that treatment of OVX guinea pigs with low doses of estradiol-17p, administered as pulses, is as effective as higher doses of the hormone (estradiol-I7p in Silastic capsules, or single injections of estradiol benzoate), in priming for behavioral responsiveness to progesterone ( Wilcox, Barclay, and Feder, 1984;Olster and Blaustein, 1990a). Furthermore, the induction of progestin receptors in the VLH is similar following injections of estradiol pulses and estradiol benzoate (Olster and Blaustein, 1990a), suggesting extraordinary sensitivity of some neurons in this particular region to the progestin receptor-inducing actions of behaviorally effective estradiol pulses.…”
Section: Introductionmentioning
confidence: 85%
“…Because reproductive hormone levels cycle in female rats, however, constant-release pellets cannot be considered physiological. Indeed, daily or continuous peripheral administration of low estradiol doses or even single high doses of long-lasting estrogens such as estradiol valerate can disrupt ovarian cycling, induce pseudopregnancy, elicit progressive, aphysiological changes in several brain neurochemical receptor systems and in behavior, and greatly accelerate the degeneration of the arcuate nucleus (83,179,347,467,468,528,529,647). In contrast, a weekly cyclic estradiol injection regimen in which 10 g estradiol benzoate was injected on Tuesdays and Wednesdays and progesterone priming and sexual-receptivity tests were done on Fridays led to stable, normal levels of progestin and oxytocin receptors and in sexual receptivity (647).…”
Section: Physiological Sex Differences In Disordered Eating)mentioning
confidence: 99%
“…A p value < 0.05 was the criterion for statistical significance. (Olster and Blaustein, 1990), estradiol treatment of ORCH guinea pigs resulted in the induction of PR-IR in many cells of the VLH (Figs. 1, 2).…”
Section: Methodsmentioning
confidence: 98%
“…It was hypothesized that lower concentrations of estradiol-induced progestin receptors in the mediobasal hypothalamus and preoptic area in orchidectomized (ORCH) males contributed to the lack of behavioral responsiveness to progesterone ( Blaustein, Ryer, and Feder, 1980). However, we have found that administration of estradiol in the form of discrete pulses [in contrast to a single injection of the longer-acting estradiol benzoate ( EB)] effectively primes ORCH males to display progesterone-facilitated lordosis ( Olster and Blaustein, 1990). Furthermore, the concentrations of progestin receptors (measured by in vitro radioligand binding assay) in combined mediobasal hypothalamus and preoptic area are not different in EB-and estradiol pulse-injected males; moreover, the number of progestin receptor-immunoreactive ( PR-IR) cells in several regions within the hypothalamus and preoptic area (i.e., VLH, medial preoptic area) is actually higher following injections of behaviorally ineffective EB, as compared to behaviorally effective estradiol pulses (Olster and Blaustein, 1990).…”
Section: Introductionmentioning
confidence: 88%